Devising a numerical method for estimating the positioning accuracy of aircraft by an information- communication network of optoelectronic stations - Tevyashev, Andriy; Haluza, Oleksii; Kostaryev, Dmytro; Paramonov, Anton; Sizova, Nataliia (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the accuracy of aircraft positioning for open and covert video surveillance by an infocommunication network of optical-electronic stations along the trajectories of their movement. The task addressed is numerical assessment of the accuracy of aircraft positioning in airspace. It is proposed to use a convex polyhedron as a universal assessment of the accuracy of aircraft positioning, in which, with a given probability, the aircraft is located. It is shown that the lower estimate of this probability depends on the a priori information on the statistical properties of the errors in the estimates of the coordinates of the aircraft location, and the scattering ellipsoid, which is currently the main form of assessing the accuracy of aircraft positioning in airspace, is a special case and is always located inside a convex polyhedron. The results reported here include the following: – simulation models of open and covert video surveillance by an infocommunication network of optoelectronic stations along the trajectories of aircraft movement; – a numerical method for estimating the uncertainty region in the form of a convex polyhedron, in which, with a given probability, the aircraft is located; – dependence of change in the shapes and boundaries of the convex polyhedron on the errors of video surveillance and the mutual spatial location of the aircraft and the network of optoelectronic stations; – software implementation of methods for constructing and visualizing the shapes and boundaries of uncertainty regions in the form of convex polyhedrons and scattering ellipsoids. It is shown that the aircraft is inside the convex polyhedron with the probability P ≥ 0.8889 for any distribution, P ≥ 0.9506 for a symmetric one and P ≥ 0.9973 for a normal distribution